2019
DOI: 10.1038/s41598-019-53500-y
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Whole Exome Sequencing in a Cohort of Transgender Individuals to Identify Rare Genetic Variants

Abstract: Approximately 0.5–1.4% of natal males and 0.2–0.3% of natal females meet DSM-5 criteria for gender dysphoria, with many of these individuals self-describing as transgender men or women. Despite recent improvements both in social acceptance of transgender individuals as well as access to gender affirming therapy, progress in both areas has been hampered by poor understanding of the etiology of gender dysphoria. Prior studies have suggested a genetic contribution to gender dysphoria, but previously proposed cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 50 publications
(53 reference statements)
1
23
0
1
Order By: Relevance
“…Nevertheless, because of the temporal nature of this linking and the consecutive organization of body and brain, the two processes can be influenced independently. In a tiny percentage of people, 0.5-1.4% of natal males and 0.2-0.3% of natal females (Theisen et al, 2019), this alignment is unconventional.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, because of the temporal nature of this linking and the consecutive organization of body and brain, the two processes can be influenced independently. In a tiny percentage of people, 0.5-1.4% of natal males and 0.2-0.3% of natal females (Theisen et al, 2019), this alignment is unconventional.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it may be hypothesized that biological factors that act during intrauterine or early development and are involved in the development of gender dysphoria, are also related to bone development programming. For example, a whole-exome sequencing study in transgender individuals found 21 variants in 19 genes associated with estrogen activated pathways of sexually dimorphic brain development ( 20 ). These variants in estrogen receptor–activated pathways might also play a role in bone mineral acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Los aportes teóricos de la hoy se denomina discordancia de género se pueden categorizar en tres grupos. Los estudios médico-esencialistas (Fine, 2011;De Vicente, Berdullas y Castilla, 2012;García Falgueras et al, 2005;Segovia y Guillamón, 1993;Zubiaurre-Elorza et al, 2013;Carrillo et al, 2010;Bao y Swaab, 2011;Fernández y Pásaro, 2017;Junger, et al 2014;Smith, Junger, Derntl y Habel, 2015;Theisen, et al 2019) que afirman que las características biológicas (genético-anatomofisiológicas) de las personas son inalterables y anteriores a la cultura, así como la hipótesis del determinismo genético, hormonal y cerebral de la identidad sexo-genérica y su inmutabilidad.…”
Section: Enfoques Teóricos Y Posturas Críticas Antagónicasunclassified